Strategies of Adaptation and Resilience for Sharia Entrepreneurship at the Minimarket Business Unit of Pondok Modern Darussalam Gontor Putri 1 - Achmad Fajaruddin; Ahmad Suminto (International Journal of Business and Quality Research, 2026)
This study aims to analyze the Sharia-based entrepreneurial resilience strategies of the mini-market business unit at Pondok Modern Darussalam Gontor Putri 1 (Mantingan, Ngawi) in navigating economic dynamics, as well as to examine the implementation of Sharia principles in its management. A qualitative approach with a case study design was employed. Data were gathered through in-depth interviews, participant observation, and document analysis, and subsequently analyzed using thematic analysis techniques. The findings indicate that the business unit's resilience is built upon four key strategies: the digitalization of operations and marketing; product and service diversification; the strengthening of management and human resources; and the consistent application of Standard Operating Procedures (SOPs). These strategies enable the business unit to maintain sustainability amidst economic shifts, price fluctuations, and changing consumer needs. The implementation of Sharia principles is reflected in the adherence to values ​​such as honesty, trustworthiness, fairness, and transparency; the avoidance of riba (usury) and gharar (uncertainty/ambiguity); and the provision of halal (permissible) and tayyib (wholesome) products. Beyond its function as an economic unit, the mini-market serves as a medium for entrepreneurial learning for female students (santriwati) through the integration of character education, Islamic business ethics, and managerial practice. This study affirms that the pesantren-based Sharia entrepreneurship model possesses strong adaptive capacity to build business resilience while simultaneously generating sustainable economic, educational, and social value.